Charles Darwin and lady hope — the legend still alive - Malec, Grzegorz (Hybris, 2015)
The theme of the present paper is the story of Darwin’s conversion as spread by Elizabeth Hope. Her article was published in August 1915. She wrote under the pseudonym “Lady Hope”, and her paper was titled “Darwin and Christianity”. Elizabeth Hope claimed that she visited Charles Darwin in autumn 1881, a couple of months before his death. Darwin during her visit was supposedly bedfast and reading Hebrews. During their conversation Darwin allegedly asked her to speak about Jesus Christ and sing some hymns in his summer house. I claim that (1) strong arguments exist that Lady Hope’s story is only the fruit of her imagination, and (2) all her adherents can only have hope that Darwin, renouncing his theory, returned to Christianity. Finally, I show some unpublished opinions of modern scholars which indicate that Darwin’s conversion never took place, and he never rejected his theory of evolution by natural selection.